Re-establishing the Relevance of Philippine Coast Guard Civil Relations Service Basic Training Course Towards its Enhancement - de la Rosa-Mesa, Lovely Gay B (Future Science / FSH-PH Publications, 2025)
The Philippine Coast Guard (PCG) has been involved in civil relations activities to foster community partnerships and support nation-building. Realizing the need to have skilled personnel embodied with fundamental pillars of civil elations, the Civil Relations Service Basic Training Course (CRSBTC) was developed in 2020. This study aims to re-establish the relevance of CRSBTC by assessing its learning outcomes, course content, and work applicability. Utilizing a Mixed-Method Research Design, this study collected data through surveys and interviews from CRSBTC Graduates, CRSBTC Proponents, Armed Forces of the Philippines Civil Military Operations (AFPCMO) and National Service Training Program -Civic Welfare Training Service (NSTP-CWTS) Instructors Training Course Graduates, District Commanders, Philippine Coast Guard Auxiliary (PCGA), CRS personnel with no training and Training Managers. Results revealed that the CRSBTC is highly effective in equipping graduates with knowledge and skills while highlighting areas for improvement. Further, the CRSBTC is highly relevant to PCG in CRS performance, community engagement and enhancing personnel capabilities. The challenges in implementing the Course includes underdeveloped and unapproved POI, lack of qualified instructors, COVID-19 pandemic, lack of budgetary support and conducive training facilities, and students taking multiple courses. Meanwhile, the recommendations include updating of POI with CRS-work related topics, adopting CRSBTC as a specialization course, developing a pool of qualified instructors, providing adequate training facilities, integrating technology, and studying the best practices from other uniformed service. Finally, a Course Instructional Guide for CRSBTC was developed and proposed for adoption and institutionalization to serve as a blueprint for CGCRS training.